IMPLEMENTASI PROGRAM JAMINAN PERSALINAN (JAMPERSAL) DI KABUPATEN GROBOGAN (2011-2013) - Efik Yuli Prastiwi; Achmad Taufiq; Puji Astuti (Journal of Politic and Government Studies, 2014)
In accepting administration fund JAMKESMAS and Jampersal in basicservices year 2011, Grobogan Regency got Jampersal fund for the first phase Rp1.462.179.000,00 and second phrase Rp 1.949.572.000,00, while in 2012,Grobogan got Jampersal fund for the first phase Rp 2.375.331.000,00 and thesecond phase Rp 3.167.108.000,00.However, the infant mortality rate (IMR) had increased from year 2011amounted to 8,78 per 1.000 life birth, in 2012 amounted to 10,60 per 1.000 lifebirth, and in 2013 amounted to 14,4 per 1.000 life birth. Meanwhile, maternalmortality rate (MMR) increased significantly in year 2011 by 114,04 per 100.000life birth. This is a concern why there is no real evidence of Jampersal program.In study of Implementation of Jampersal Program, the writer uses qualitativemethod. The analysis method which is used is exploratory study based on in-depthinterviews, documents examination, and triangulation.The result of this analysis shows that Jampersal is not effective yet inreducing the infant mortality rate (IMR) in Grobogan Regency caused byinhibiting factors in implementing the Jampersal program. The inhibiting factorswhich come from the implementer are claim report problems, less effectivesocialization, poor communication in PPK, 25% funding cut in 2012, as well asthe delay in receiving fund claim. In addition, the inhibiting factors coming from2Jampersal users are people’s habit of not doing check up after child birth andexamination after baby newborn, expectant mothers’ habit of massaging theabdominal area, and the habit of using dukun beranak.Keywords: Jampersal, Program Implementation, Grobogan Regency